Let's talk about teasing - Berry, Joy Wilt.; Costanza, John (Chicago : Childrens Press, 1985)
Explains to children what teasing is and why it is better not to tease people. "If you can't say something nice, don't say anything at all."
3.5
K-3
Keywords: Human behavior -- Juvenile literature; Behavior; Human behavior